Исследование магнитных свойств композиционных материалов на основе гексагонального феррита Z-типа - Лемешов, Владислав Вадимович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
Composite materials based on Ba3Co1.9Ti0.4Fe23.7O41 hexaferrite and BaTiO3 ferroelectric were fabricated. Their magnetic properties were studied using a pulsed magnetometer. Spectra of reflection coefficients of samples of composite materials have been studied. As a result, it was shown that these materials can be used as absorbers of electromagnetic radiation.